Pemberian Dosis Mokroorganisme Selulotik dan Anorganik Dosis Rendah Pada Tanaman Kelapa Sawit (Elaeis guineensis jacq) di Tbm-II - Joko Pranoto; Gusmawartati '; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The study aimed to determine the effect of cellulolytic microorganisms given and low doses of inorganic and the single factor on the growth of oil palm plantations in TBM-II. The study implemented in PT. Tunggal Perkasa Plantation, Air Molek, District pasir penyu, Indragiri Hulu, Riau Province. It was conducted from October 2012 to January 2013. The study uses Completely Randomized Design (CRD) with two factors namely cellulolytic microorganisms and low doses of inorganic fertilizers with 3 replications. Data were analyzed using ANOVA and followed by further test DNMRT at 5% level. The parameters measured were the increase of hump circumference, leaf length, increase number of leaves, number of leaflets, leaf width and length of the child leaves. The results of the study showed that giving cellulolytic microorganisms and  low of doses inorganic fertilizer had no significant effect on all parameters of the observations, also the single factor low doses of inorganic fertilizer, but it is given significant effect on the single factor giving cellulolytic microorganisms to parameter in increasing of hump circumference and length of the leaves with 10 ml/plant of doses. Keywords : Cellulolytic microorganisms, low doses of inorganic fertilizer and oil palm.